Powered Flight The Engineering of Aerospace Propulsion - Greatrix, David R. (Springer London : Imprint: Springer, 2012)
Whilst most contemporary books in the aerospace propulsion field are dedicated primarily to gas turbine engines, there is often little or no coverage of other propulsion systems and devices such as propeller and helicopter rotors or detailed attention to rocket engines. By taking a wider viewpoint, Powered Flight - The Engineering of Aerospace Propulsion aims to provide a broader context, allowing observations and comparisons to be made across systems that are overlooked by focusing on a single aspect alone. The physics and history of aerospace propulsion are built on step-by-step, coupled with the development of an appreciation for the mathematics involved in the science and engineering of propulsion. Combining the author's experience as a researcher, an industry professional and a lecturer in graduate and undergraduate aerospace engineering, Powered Flight - The Engineering of Aerospace Propulsion covers its subject matter both theoretically and with an awareness of the practicalities of the industry. To ensure that the content is clear, representative but also interesting the text is complimented by a range of relevant graphs and photographs  including  representative engineering, in addition to several propeller performance charts. These items provide excellent reference and support materials for graduate and undergraduate projects and exercises. Students in the field of aerospace engineering will find that Powered Flight - The Engineering of Aerospace Propulsion supports their studies from the introductory stage and throughout more intensive follow-on studies.